PENGARUH PROMOSI, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN E-COMMERCE SHOPEE DI BOYOLALI - Dahlia Rahmawati; Pemilia Sulistyowati (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to determine and analyze the direct effect of promotions on Shopee customer satisfaction in Boyolali, to determine and analyze the direct effect of price perception on Shopee customer satisfaction in Boyolali, to determine and analyze the direct effect of service quality on Shopee customer satisfaction in Boyolali and to determine and analyze the simultaneous effect of promotions, price perception, and service quality on Shopee customer satisfaction in Boyolali. This study uses a quantitative method with a sample of 80 consumer respondents in Boyolali District which is the city center of Boyolali Regency. Data were analyzed using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, normality tests, multiple linear regression analysis tests, T tests, F tests, R2 determination coefficient tests using IBM SPSS Statistics. The results of the study show that directly promotions have a significant effect on Shopee e-commerce customer satisfaction in Boyolali, directly price perceptions have a significant effect on Shopee e-commerce customer satisfaction in Boyolali, directly service quality has a significant effect on Shopee e-commerce customer satisfaction in Boyolali, and directly and simultaneously promotions, price perceptions and service quality have a significant effect on Shopee e-commerce customer satisfaction in Boyolali.